Motivasi Mengajar pada Relawan di Sekolah Alam Dyatame - Erton Umda Saputra; R. Pasifikus Ch. Wijaya; Shela C. Pello; Serlie K.A Littik (Jurnal Global Ilmiah, 2025)
Seeing the educational problems that occur in Indonesia, especially in the Province of East Nusa Tenggara, a non-formal school, namely the Dyatame Nature School, was established on Sumba Island to help overcome the illiteracy rate. The purpose of this study is to determine and describe the teaching motivation of volunteers at the Dyatame Nature School. The method in this study is qualitative with a phenomenological approach, using in-depth interview data collection techniques with 5 volunteer participants. The analysis technique used is IPA (Interpretative Phenomenological Analysis). The results show that intrinsic volunteer motivation includes personal satisfaction, recognition, social responsibility, self-development, childhood experiences, and hope. While extrinsic motivation includes a conducive learning environment, social support, interpersonal relationships, children's development, socioeconomic conditions, and mutual cooperation culture. This research provides practical implications for the development of volunteer-based education programs.